Double-layer coating for nuts preservation: covalently grafted resveratrol for antioxidant activity and protein-polysaccharide complexes for high barrier properties - Yunze Ma; Jian Li; Rui Zhao; Huajiang Zhang; Zhanhui Geng; Hanyu Li; Yuepeng Wang; Ning Xia; Lina Xu (Food Research International, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Dual signal-enhanced immunochromatographic test strip based on Au@PtNPs: From sensitive detection of thiamethoxam to multiplex pesticide screening in vegetables - Zhengtao Li; Lingjun Geng; Jiashuai Sun; Jingcheng Huang; Rui Xu; Zhen Guo; Shouyi Dou; Liying Zhang; Fangling Du; Yemin Guo; Xia Sun; Nortoji A. Khujamshukurov (Food Chemistry, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Potential of Bacillus amyloliquefaciens XSZ-1 as a bio-inoculant for enhancing cotton productivity and health in saline-alkali cotton field soil - Jiayue Yuan; Jiali Lu; Zekun Ma; Yanlei Zhu; Xu Geng; Bei Zheng; Rui Zhang (World Journal of Microbiology and Biotechnology, 2026)

Establishment and comprehensive performance evaluation of auto- and allo-tetraploids derived from Crassostrea gigas and C. angulata - Xianchao Bai; Yuanxin Liang; Geng Cheng; Jianmin Zhou; Rui Xu; Qi Li (Aquaculture International, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Luminescent hydrogel-enabled electrochemiluminescent aptasensor and portable analyzer for on-site quantification of acetamiprid in vegetables - Jiashuai Sun; Lingjun Geng; Jingcheng Huang; Zhen Guo; Rui Xu; Zhiping Yu; Zhengtao Li; Peisen Li; Pengwei Zhang; Shengkun Ren; Elena Zavyalova; Yemin Guo; et al. (Journal of Hazardous Materials, 2026)

Multifaceted roles of CcGpi7, a phosphoethanolamine transferase, in physiology and virulence of Corynespora cassiicola - Chao Xu; Mengyuan Hou; Qingzhou Ma; Yue-hua Geng; Rui Zang; Taibo Liang; Yashuang Guo; Mengmeng Yang; Meng Zhang (World Journal of Microbiology and Biotechnology, 2026)

Structural determinants of gelation kinetics in rambutan seed starches: Implications for enhanced precision in 3D food printing - Rui He; Yuxuan Li; Xiaoyu Lin; Bo Xu; Xiang Huo; Weiming Zhang; Tao Yang; Geng Zhong; Fengwei Xie; Ying Chen (Carbohydrate Polymers, 2026)

BsSYT1 is required for growth, conidiogenesis, stress response and virulence of Bipolaris sorokiniana - Yuehua Geng; Feiyu Yan; Yu Zhang; Mengyao Yang; Changshui Li; Ruilin Shi; Chao Xu; Rui Zang; Qin Guo; Yashuang Guo; Qingzhou Ma; Meng Zhang (World Journal of Microbiology and Biotechnology, 2026)

High breeding potential for growth exists in normal, black, and golden shell lines of tetraploid Fujian oyster revealed through three generations of mass selection - Yuanxin Liang; Qi Li; Xianchao Bai; Geng Cheng; Jianmin Zhou; Rui Xu; Fanzhi Chu; Zhiyang Cui; Chengxun Xu; Wenshu Luo (Aquaculture, 2026)

Harvesting organic chelated calcium from sewage sludge for plant germination by alkaline-thermal treatments - Rui Liu; Ying Xu; Jiaqi Gao; Hui Geng; Liang Song; Yue Zhang; Xiaohu Dai (Journal of Environmental Sciences, 2026)

Drivers of CO2 and CH4 fluxes from shallow lakes and prediction based on climate factors under global warming - Zhentao Wu; Hui Liu; Fan Yang; Rui Ran; Huimin Yu; Haonan Xu; Danyun Chen; Geng Wang; Xiaobing Pang (Journal of Environmental Sciences, 2026)

High-performance composite adsorbent for the identification and enrichment of fenthion and its main metabolites - Lingjun Geng; Pengwei Zhang; Qingxia Han; Haifang Wang; Jingcheng Huang; Rui Xu; Jicheng Zhao; Yemin Guo; Xia Sun; Fangling Du (Journal of Hazardous Materials, 2026)

Mechanisms of AMF-mediated correlation between nutrient uptake and soil micropatterns in sugar beet plants under rotational and continuous cropping soil environments - Rui Chen; Yonglong Liu; Xinyi Zhang; Gui Geng; Lihua Yu; Yao Xu; Jiahui Liu; Yuguang Wang (Journal of Cleaner Production, 2026)

The protective role of HINT2 in hypoxia injury of neuroblastoma cells and its regulatory mechanism on MCU-MICU1 pathway - Shao Rui; Zhang Lilong; Geng Yannan; Xu Tiantong (Neurophysiology, 2025)

A novel interpolation method for high temporal-resolution electricity usages based on volatility quantification and pattern extraction - Yinao Zhou; Ruoxi Geng; Xuyuan Kang; Huiming Xu; Xiao Wang; Rui Li; Da Yan (Energy and Buildings, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

GO-SELEX-enhanced dual-recognition sensor for highly specific detection of azamethiphos - Lingjun Geng; Jingcheng Huang; Haowei Dong; Haifang Wang; Rui Xu; Zhiping Yu; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Journal of Hazardous Materials, 2025)

Dual-recognition strategy sensor based on GO-SELEX aptamer screening for high-specificity identification of fenthion and its major metabolites in vegetables - Lingjun Geng; Haowei Dong; Qingxia Han; Xue Huang; Jingcheng Huang; Haifang Wang; Rui Xu; Jicheng Zhao; Zhouping Wang; Shijia Wu; Ibrahim A. Darwish; Yemin Guo; et al. (Food Bioscience, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Integrative transcriptomic and physiological analyses uncover mechanisms by which arbuscular mycorrhizal fungi mitigate salt stress in sugar beet - Zeyuan Cui; Xiaodong Li; Pingan Han; Rui Chen; Yinzhuang Dong; Gui Geng; Lihua Yu; Jiahui Liu; Yao Xu; Yuguang Wang (Mycorrhiza, 2025)

Biochar@MIL-88A(Fe) accelerates direct interspecies electron transfer and hydrogen transfer in waste activated sludge anaerobic digestion: Exploring electron transfer and biomolecular mechanisms - Weihang Xu; Lan Wu; Mengqi Geng; Junmei Zhou; Sai Bai; Duc Viet Nguyen; Rui Ma; Di Wu; Jin Qian (Environmental Research, 2025)

Preparation strategy of molecularly imprinted polymers adsorbent based on multifunctional carrier for precise identification and enrichment of fenthion - Lingjun Geng; Jingjing Liu; Jingcheng Huang; Haifang Wang; Peisen Li; Rui Xu; Chengqiang Li; Haowei Dong; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Food Chemistry, 2025)

Construction of low-toxicity cadmium sulfide/nitrogen-doped muti-walled carbon nanotubes for peroxymonosulfate activation: The crucial role of electron transfer - Jin Qian; Sai Bai; Mengqi Geng; Dandan Zhang; Guoping Xiang; Yichu Zhang; Yangju Li; Dongdong Chu; Di Wu; Rui Ma; Yueping Bao; Xiangning Xu; et al. (Environmental Research, 2025)

A ship motion forecasting approach based on Fourier transform, regularized Bi-LSTM and chaotic quantum adaptive WOA - Ming-Wei Li; Rui-Zhe Xu; Jing Geng; Wei-Chiang Hong; He Li (Ocean Engineering, 2024)

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

Arbuscular Mycorrhizal Fungi Enhance Tolerance to Drought Stress by Altering the Physiological and Biochemical Characteristics of Sugar Beet - Zeyuan Cui; Rui Chen; Tai Li; Bingchen Zou; Gui Geng; Yao Xu; Piergiorgio Stevanato; Lihua Yu; Vadim N. Nurminsky; Jiahui Liu; Yuguang Wang (Sugar Tech, 2024)

Magnetic porous microspheres altering interfacial thermodynamics of sewage sludge to drive metabolic cooperation for efficient methanogenesis - Hui Geng; Ying Xu; Rui Liu; Jun Xu; Xiang Li; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Effects of pH-varying thermal modification on sewage sludge: A focus on releasing nitrogen- and phosphorus-containing substances - Rui Liu; Ying Xu; Jiachang Cao; Hui Geng; Renjie Chen; Haoyu Liu; Yongdong Chen; Shijie Yuan; Xiaohu Dai (Water Research, 2024)

Evaporation-driven interfacial restructuring induces highly efficient methanogenesis of waste biomass - Ying Xu; Haoyu Liu; Hui Geng; Rui Liu; Xiaohu Dai (Water Research, 2024)

Magnetic porous microspheres enhancing the anaerobic digestion of sewage sludge: Synergistic free and attached methanogenic consortia - Hui Geng; Ying Xu; Rui Liu; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Comparative toxicology of algal cell extracts and pure cyanotoxins: insights into toxic effects and mechanisms of harmful cyanobacteria Raphidiopsis raciborskii - Zhongshi He; Youxin Chen; Jin Gao; Yewei Xu; Xinya Zhou; Rui Yang; Ruozhen Geng; Renhui Li; Gongliang Yu (Harmful Algae, 2024)

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

Neonicotinoids: Advances in hazards of residues, screening of aptamers and design of aptasensors - Jingcheng Huang; Haifang Wang; Haowei Dong; Mengyue Liu; Lingjun Geng; Jiashuai Sun; Zhen Guo; Rui Xu; Giovanna Marrazza; Xia Sun; Yemin Guo (Trends in Food Science & Technology, 2024)

GABRP Promotes the Metastasis of Pancreatic Cancer by Activation of the MEK/ERK Signaling Pathway - Yong Meng; Rui Li; Shuaiming Geng; Wenhao Chen; Weirong Jiang; Zhiwen Li; Ji Hao; Zhen Xu (Biochemical Genetics, 2024)

Cation exchange resins enhance anaerobic digestion of sewage sludge: Roles in sequential recovery of hydrogen and methane - Hui Geng; Ying Xu; Rui Liu; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Intrinsic reaction selectivity between gaseous HCl and SO2 over ethanol-hydrated CaO adsorbent in coal-fired flue gas dechlorination - Xiaoshuo Liu; Rui Wang; Xinze Geng; Ao Shen; Cong Chen; Yifan Xu; Xunlei Ding; Yufeng Duan; Shilin Zhao (Chemical Engineering Journal, 2023)

Neglected Adult Tinea Capitis in South China: A Retrospective Study in Nanchang, Jiangxi Province, from 2007 to 2021 - Yun Jin; Chengfang Geng; Oliver Blechert; Qing Jiang; Rui Xu; Yunpeng Luo; Xinyi Fan; Guirong Qiu; Ping Zhan (Mycopathologia, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

The draft genome sequence and characterization of Exserohilum rostratum, a new causal agent of maize leaf spot disease in Chinese Mainland - Qingzhou Ma; Chongyang Cheng; Yuehua Geng; Rui Zang; Yashuang Guo; Lixin Yan; Chao Xu; Meng Zhang; Haiyan Wu (European Journal of Plant Pathology, 2023)

The interplay of particle properties and solution chemistry on aggregation kinetics of soil nanoparticles - Ning Hu; Chen-yang Xu; Zeng-chao Geng; Fei-nan Hu; Qi-rui Li; Ren-tian Ma; Qiang Wang (Journal of Soils and Sediments, 2022)

Toward Exploring Topographic Effects on Evolution and Propagation of Ocean Mesoscale Eddies Through Life Cycle Across Izu-Ogasawara Ridge in Northwestern Pacific Ocean - Rui Nian; Xue Geng; Zhengguang Zhang; Minghan Yuan; Zhen Fu; Hengfu Xu; Hua Yang; Qi Lai; Hui He; Chi Wei Su; Lina Zang; Qiang Yuan; et al. (Frontiers in Marine Science, 2022)
Ocean mesoscale eddies contribute significantly to water transport on a global scale, constituting the ubiquitous, irregular, discrete, nonlinear components. In this manuscript, we propose to explore whether and how the topographic effect of one meridional ridge, could exert considerable influences on the evolution and propagation of mesoscale eddies through their life cycle, directly from the perspectives of real observation statistics. We systematically investigate the known variability of mesoscale eddy trajectories, derived by multimission satellite altimetry from 1993 to 2018, of a life cycle more than 6 months, over the Izu-Ogasawara Ridge, and quantitatively examined the eddy-ridge interaction by observation statistics and wavelet coherence map, with respect to the intrinsic attributes, namely, the amplitude, the rotation speed, the radius. Due to the spatial-temporal diversity, a series of correlative steps have been particularly designed along time-frequency domain to trace back mesoscale eddy trajectories in a variety of origins, location, lifespan, polarity, either completely or partially passing over the ridge, and to facilitate the standardization in statistics across three phases of their life cycle, i.e., before, during and after the interaction with the ridge. It has been revealed in our experiment that three intrinsic attributes of mesoscale eddies within 25 years, all demonstrated noticeable correlation with the variation of topographic relief over the ridge. We observed that most of the cyclonic eddies obviously tended to begin to decay or even demise, while on the contrary, some of the anticyclonic eddies preferred to intensify slightly, or making no significant difference when encountering the upslope until climbing across the top, basically consistent with the expectation of potential vorticity (PV) conservation. The drifting velocity agreed with the tendency that the direction would be more probably modified toward equatorward or poleward by forcing to meridional component, with zonal component reduced at the beginning. The mesoscale eddies with the passage over the ridge exhibited the relatively high average horizontal scales, amplitude, rotation speed on the whole, compared to those with only partially passage. The developed scheme could integrate more evidences on how mesoscale eddies response to the topographic effects during their time-varying evolution and propagation process, and help provide opportunities to potentially identify and predict the underlying dynamic patterns and mechanisms that mesoscale eddies engage in ocean dynamics when proceeding toward meridional ridges on a global scale, with the promise of the end-to-end data-driven solution, such as deep learning architecture involved in the future.

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

Clarification of the etiology of peach bacteria leaf shot hole caused by Pantoea spp. in Henan Province, China, based on morphological characteristics and multi-locus sequences analysis - Rui Zang; Lu-lu Song; Chao Xu; Xin-ming Yin; Zhan-xiang Qiao; Yue-hua Geng; Meng Zhang (European Journal of Plant Pathology, 2021)

Dynamic simulation of tropical coral reef ecosystem being disturbed by multiple situations - Geng Wang; Rui Dong; Huimin Xu; Dewen Ding (Acta Oceanologica Sinica, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Complete genome sequence of a novel mycovirus isolated from the phytopathogenic fungus Corynespora cassiicola in China - Yanfen Wang; Hang Zhao; Caiying Xue; Chao Xu; Yuehua Geng; Rui Zang; Yuxia Guo; Haiyan Wu; Meng Zhang (Archives of Virology, 2020)

Comparisons of Evaluation Factors and Application Effects of the New [BQ]GSI System with International Rock Mass Classification Systems - Shen Yan-jun; Yan Rui-xin; Yang Geng-she; Xu Guang-li; Wang Shan-yong (Geotechnical and Geological Engineering, 2017)

PAHs in PM2.5 in Zhengzhou: concentration, carcinogenic risk analysis, and source apportionment - Jia Wang; Ning Bo Geng; Yi Fei Xu; Wen Ding Zhang; Xiao Yan Tang; Rui Qin Zhang (Environmental Monitoring and Assessment, 2014)

Microbial community structure and diversity in a native forest wood-decomposed hollow-stump ecosystem - Bao-Yu Tian; Qin-Geng Huang; Yan Xu; Chun-Xiang Wang; Rui-Rui Lv; Jian-Zhong Huang (World Journal of Microbiology and Biotechnology, 2010)